In Vitro Digesting Measurement of Cassava Leaves Using Gizzard Fluid and Chicken Duodenum - Ali Mursyid Wahyu Mulyono; Engkus Ainul Yakin; Muhammad Affan Azizy Hasibuan (Bantara Journal of Animal Science, 2021)
Cassava leaves are an alternative feed material that can be a feed material with sufficient protein content. The study aimed to determine the effect of gizzard and duodenal fluids on in vitro digesting measurements of cassava leaves. The study used a Complete Randomized Design (RAL) unidirectional pattern, Variance Analysis (ANOVA) with Duncan's Multiple Range Terst (DMRT) follow-up test using the SPSS application. The study used 4 treatments and 3 repeats: P0: No digestive fluids (controls), P1: Gizzard fluid, P2: Duodenal fluid, P3: A mixture of gizzard and duodenal fluids. The observed variables are the Dry Material Digest Coefficient (KCBK), the Organic Material Digest Coefficient (KCBO), and the Dissolved Protein Digest Coefficient (KCPT). The results of the study that the use of gizzard fluid in in vitro digestion measurements was better in increasing the value of in vitro digestant of cassava leaves. The use of gizzard fluid can increase the digestibility coefficient of organic matter (KCBO) by 21.2160% and the dissolved protein digest coefficient (KCPT) by 50.4620%.